Scaling equation for viscosity of polydimethylsiloxane in ethyl acetate: From dilute to concentrated solutions. (26th August 2020) - Agasty, Airit; Wisniewska, Agnieszka; Kalwarczyk, Tomasz; Koynov, Kaloian; Holyst, Robert
Abstract: Rheology of polymer solutions suffers from lack of universal model of viscosity applicable across wide range of concentrations. Here we build such a model on the basis of measured viscosity of polydimethylosiloxane (PDMS) in ethyl acetate in a wide range of polymer concentrations: from dilute up to highly concentrated solutions. The relationship between viscosity and different polymer parameters in solution such as coil size, correlation length ξ, monomer–solvent and monomer–monomer interaction parameter were established experimentally as a function of concentrations [from 0.001 g ∕ c m 3 to 8.000 g ∕ c m 3 ], temperature [in a range 283–303K] and molecular masses [9–139 k g ∕ m o l ]. Entanglement onset at the crossover from dilute to semi-dilute solution as well as the solvent–monomer contact reduction at the crossover from semi-dilute to concentrated regime are captured by the model. This model is in accordance with the Eyring rate theory for activated processes. Graphical abstract: Highlights: A proposed scaling model to describe polymer characteristics through viscosity. Utilizes well-described polymer dimensional structures in solutions. Model extends from dilute to concentrated solutions, for various molecular weights. Increased knowledge of interaction and scaling parameters. Applicable for universal quick polymer characterization.